Water supply system in Międzychód commune = System zaopatrzenia w wodę w gminie Międzychód - Ogiołda, Ewa; Nowogoński, Ireneusz; Leszczyńska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The properly designed and exploited water supply system is very important both for consumers and management in commune. Work conditions of such systems are changing so it is necessary to know its current parameters. Now we have different modern programs which make possible to calculate parameters and carry out simulation of designed changes which could improve reliability coefficients. Evaluation of exploited water supply system in Międzychód and designed its connection with subsystem in Radgoszcz were presented in this paper.
Keywords: system zaopatrzenia w wodę; obliczenia hydrauliczne; obliczenia symulacyjne; Międzychód; water supply system; hydraulic calculation; numerical simulation